Dengue infection in a patient with systemic lupus erythematosus: a case report: Infección por dengue en un paciente con lupus eritematoso sistémico: reporte de caso - García-Galicia, Carlos Alberto (2024)
Systemic Lupus Erythematosus (SLE) is an autoimmune disease caused by an autoreactive B and T cell response with loss of immune tolerance to self-antigens. It manifests with asthenia, fever, myalgias, arthralgias, skin rash and fatal organ damage. Dengue is a zoonotic disease caused by the dengue virus (DENV), transmitted by mosquitoes of the Aedes aegypti species. Diagnostic suspicion is made in the presence of acute febrile syndrome with clinical manifestations and demographic history. Confirmation is by detection of the virus by PCR-RT, or of the structural protein NS1. The present case report is a 58-year-old woman with data of lupus exacerbation and with clinical manifestations suggestive of Dengue fever, with a history of travel to an endemic area. The confirmatory PCR-RT test leads to appropriate medical treatment. The importance of the case lies in differentiating the diagnosis in a timely manner.